Antiplatelet Therapy in the Secondary Prevention of Non-cardioembolic Ischemic Stroke and Transient Ischemic Attack: A Mini-Review - Vališ, Martin; Klímová, Blanka; Novotný, Michal; Herzig, Roman (Frontiers in Neurology, 2021)
Stroke is the leading cause of long disability. Therefore, the purpose of this mini-review is to discuss the main antiplatelet agents, which have been successfully used in the prevention of noncardioembolic ischemic stroke and transient ischemic attack (TIA). The methodology is based on a literature review of available peer-reviewed English written studies found in Pub Med. The findings reveal that aspirin remains a reliable antiplatelet agent in the secondary prevention of acute noncardioembolic ischemic stroke and TIA, however, they also illustrate a preference for other agents (i.e., ticagrelor, clopidegrol and cilostazol) than only aspirin, both in antiplatelet mono and dual therapies with aspirin. In addition, the results indicate that time is an important factor not only in severe stroke, but also in non-severe stroke and TIA, which suggests that antiplatelet therapy should be applied within 24 hours after the first symptoms because early treatment can lead to the improvement in neurological outcome and decrease in the risk of early subsequent stroke.